The New Internationalists: World Vision and the Revival of American Evangelical Humanitarianism, 1950–2010 - David King (Religions, 2012)
International relief and development agencies consistently rank among the largest evangelical organizations, and in recent decades, they have gained increased exposure and influence within the greater humanitarian community. World Vision, the largest evangelical agency, is also the largest Christian humanitarian organization in the world. Themes of politics and culture wars have led many to scholars to categorize American evangelicals into distinct conservative and liberal parties. Yet the history of American evangelicals’ humanitarianism demonstrates how they often resisted such dichotomies. As evangelical humanitarian agencies expanded exponentially over the past five decades, they came to embrace a “holistic gospel” that helped shape evangelical mission debates concerning the relationship between evangelism and social action; they engaged international evangelicals that forced Americans to reconsider their own categories; and many modeled a practical ecumenism that allowed evangelicals to expand beyond a limited subculture to work alongside other religious and even secular NGOs. While other evangelical progressives fragmented over identity politics or remained tethered to small alterative communities, the leading aid agencies have achieved broad support across evangelicalism, making them some of the most influential voices.